(3cJGH ObGFb GdMbGFbs - (3Ydj Hf eMeO Hf SGde GdJZdHj, CHh GdMSf, Sja GdOjf GdBeOj,J (B631 (3g` s
(3ChdgG (B:s
(3hHYO aEfg deG cKQ SYa CHfGA ReGffG hYdeGA ChGffG HGdfXQ ai Ydhe GdChdjf s
(3BNQgG (B:s
(3hPdc ceG ai GdCSJbQG h GdJLQHI aEfgeG jhUdGf Edi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B155s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B758s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI HQjfSJhf (B(828(428)) s
Keywords: (3GdadSaI hGdefWbs